(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to- Preparing an educational curriculum using the method of self-review in acquiring learning some ground movements in artistic gymnastics.- To identify the impact of the educational curriculum prepared using the self-review method in acquiring learning some floor movements in artistic gymnastics.The researchers used the experimental approach due to its suitability to the nature of the research problem, as the research community consisted of students of the fifth grade of primary school, Al-Urwa Al-Wuthqa Primary School for Boys, Directorate of Education of Al-Rusafa III, Baghdad Governorate, for the academic year 2014-2015, of 105 students divided into three divisions. The research sample was chosen randomly from the two divisions (A c) For the two groups to be experimental and control, with (20) students for each group, equivalence was conducted between the members of the two groups in the variables (age, height, mass).